2020
DOI: 10.1088/1538-3873/ab55f1
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Polarimetry of the 2017 Solar Eclipse with the RIT Polarization Imaging Camera

Abstract: In the last decade, imaging polarimeters based on micropolarizer arrays have been developed for use in terrestrial remote sensing and metrology applications. Micropolarizer-based sensors are dramatically smaller and more mechanically robust than other polarimeters with similar spectral response and snapshot capability.To determine the suitability of these new polarimeters for astronomical applications, we developed the RIT Polarization Imaging Camera to investigate the performance of these devices, with a spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…The above remarks tend to favor the polarimetric method provided it can be performed at a high spatial resolution and at a high cadence, an improvement that would also benefit to the three-dimensional reconstruction of CMEs based on their polarization. In that respect, advanced techniques as implemented at recent solar eclipses, such as micro-polarizer arrays affixed to the sensor (Burkepile et al,2017;Vorobiev et al 2017) should be considered for future space coronagraphs. This should lead to more photometrically accurate maps of the K-corona as well as of the polarized radiance pB.…”
Section: Discussionmentioning
confidence: 99%
“…The above remarks tend to favor the polarimetric method provided it can be performed at a high spatial resolution and at a high cadence, an improvement that would also benefit to the three-dimensional reconstruction of CMEs based on their polarization. In that respect, advanced techniques as implemented at recent solar eclipses, such as micro-polarizer arrays affixed to the sensor (Burkepile et al,2017;Vorobiev et al 2017) should be considered for future space coronagraphs. This should lead to more photometrically accurate maps of the K-corona as well as of the polarized radiance pB.…”
Section: Discussionmentioning
confidence: 99%
“…It has radially decreasing intensities, peaking at a few millionths of the disk intensity, and it is linearly polarized with amplitudes of 10%-70%, increasing radially. Eclipse observations by Vorobiev et al (2020) show that K-corona polarization on large spatial scales is oriented tangential to the solar limb, within measurement uncertainties. This is as expected for Thomson scattering of an unpolarized photospheric radiation field that is cylindrically symmetric relative to the radial direction, whereas the presence of symmetrybreaking features like sunspots can induce deviations in the polarization direction, as discussed in this work and by Saint-Hilaire et al (2021).…”
Section: Introductionmentioning
confidence: 62%
“…Our results therefore demonstrated that DICE is highly effective for the observation of coronal structures such as coronal morphology and polarization degree. Vorobiev et al (2020) observed the 2017 total solar eclipse in Madras, Oregon, using a polarization imaging camera equipped with Bessel B and R filters. They found that the maximum dP was 0.47 near the height of 1.5 solar radius in the eastern streamer.…”
Section: Resultsmentioning
confidence: 99%